2014
DOI: 10.1037/a0035749
|View full text |Cite
|
Sign up to set email alerts
|

Nicotine-like behavioral effects of the minor tobacco alkaloids nornicotine, anabasine, and anatabine in male rodents.

Abstract: Tobacco use is associated with lethal diseases in an estimated 440,000 persons in the United States each year (Centers for Disease Control and Prevention, 2005). Successful smoking quit-rates are estimated at 5%-8%, even though a quarter of those attempts included use of smoking-cessation aids (Messer et al., 2008; Henningfield et al., 2009). Current projections are that 16% of the U.S. population-35 million people-will still smoke in 2025, thus more effective smoking-cessation aids are urgently needed (Polloc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
56
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(64 citation statements)
references
References 55 publications
8
56
0
Order By: Relevance
“…Public Health Service, 1988). Rather, they were chosen based on their behavioral effects reported in other animal models of tobacco addiction and to establish the effective dose range in the present model (Caine et al, 2014; Dwoskin et al, 1999; Goldberg et al, 1989; Hall et al, 2014; Stolerman et al, 1995, 1984). Doses and pretreatment time were also based on a pilot study examining acute effects of these minor alkaloids on ICSS (data not shown).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Public Health Service, 1988). Rather, they were chosen based on their behavioral effects reported in other animal models of tobacco addiction and to establish the effective dose range in the present model (Caine et al, 2014; Dwoskin et al, 1999; Goldberg et al, 1989; Hall et al, 2014; Stolerman et al, 1995, 1984). Doses and pretreatment time were also based on a pilot study examining acute effects of these minor alkaloids on ICSS (data not shown).…”
Section: Methodsmentioning
confidence: 99%
“…To this end, the current study evaluated the acute effects of nicotine and the minor alkaloids nornicotine, anabasine, myosmine, anatabine, and cotinine on ICSS thresholds. Although nornicotine has been studied most extensively (e.g., Bardo et al, 1999; Dwoskin et al, 1999; Green et al, 2000), all of these minor alkaloids can produce behavioral effects under some conditions (Caine et al, 2014; Clemens et al, 2009; Goldberg et al, 1989; Hall et al, 2014; Pratt et al, 1983; Stolerman et al, 1995; Stolerman et al, 1984). …”
Section: Introductionmentioning
confidence: 99%
“…These results are consistent with those of a recent study in which intraperitoneal injection of similarly high doses of anatabine produced severe tremors and death in mice. 19 At a non-toxic dose of 1 mg/kg, anatabine increased activity across the entire session; however, the 10 mg/kg dose produced significant reductions in activity during the first 10 min of the session. When combined with the observations of overt behavior, the locomotor data suggest that behaviorally effective doses of anatabine may be relatively close to doses with acute toxicity (i.e., a narrow "therapeutic" index).…”
Section: Discussionmentioning
confidence: 99%
“…self-administration procedures, but was not reinforcing itself. [18][19][20] In summary, nicotine, cotinine, myosmine and anatabine produced distinctive patterns of effects on locomotor activity that were timeand dose-dependent. Nicotine and cotinine proved to be the most potent constituents (with lowest effective doses of 0.1 mg/kg) whereas the lowest effective doses of anatabine and myosmine were 1 mg/kg and 10 mg/kg, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation